Produksi Antosianin Tersalut Maltodekstrin Dari Kelopak Bunga Rosella (Hibiscus Sabdariffa, L.) Dan Aplikasinya Dalam Pengolahan Pangan Fungsional - Muhammad Irsyad; Mappiratu Mappiratu; Abdul Rahim (Universitas Tadulako, 2017)
Production of anthocyanin maltodextrin coating from roselle’s petals (Hibiscus Sabdariffa,L.) and application in processing functional food has been investigated. The objective’s of research were : (1) To find out extract ratio of roselle’s petals to maltodextrin which is produce anthocyanin maltodekstrin coating which has a high degree of purity and stability. (2) To find out the concentration of anthocyanin maltodextrin coaty in seaweed syrup which was produced syrup with organoleptic properties. Design of this research used one factor complete random design and group random design one factor complete random design to applied in handling influence of anthocyanin dark extract ratio of roselle’s petals to maltodextrin (v/b) (1:1; 2:1; 3:1; 4:1; and 5:1) and group random design applied in organoleptic test of functional seaweed syrup which added by various concentration of coated anthocyanin maltodextrin about (g/100 mL) (0.125; 0.25; 0.375; 0.5 and 0.625) anthocyanin and tested by 30 untrained panelist. Total analysis of coated anthocyanin maltodextrin conducted every 1 week for 8 weeks starting at week 0 using spektrofotometer UV-VIS method at 535 nm wavelength. The result of the influence of coated anthocyanin maltodextrin ratio showed anthocyanin number (highest), degree of purity (highest), and the smallest decrease in retention during storage was ratio 5:1 (v/b), then with this ratio 5:1 conducted prediction of shelf life or expiration period using kinetics reaction model, so that expiration period of coated anthocyanin maltodextrin is 28 weeks. For the best organoleptik quality of functional seaweed syrup consistently is application of coated anthocyanin maltodekstrin with anthocyanin concentration is 0,625 g/100 mL.